Healthy and sustainable food systems - Lawrence, Mark (Mark Andrew); Friel, Sharon (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This comprehensive text provides the latest research on key concepts, principles and practices for promoting healthy and sustainable food systems. There are increasing concerns about the impact of food systems on environmental sustainability and, in turn, the impact of environmental sustainability on the capacity of food systems to protect food and nutrition security into the future. The contributors to this book are leading researchers in the causes of and solutions to these challenges. As international experts in their fields, they provide in-depth analyses of the issues and evidence-informed recommendations for future policies and practices. Starting with an overview of ideas about health, sustainability and equity in relation to food systems, Healthy and Sustainable Food Systems examines what constitutes a food system, with chapters on production, manufacturing, distribution and retail, among others. The text explores health and sustainable diets, looking at issues such as overconsumption and waste. The book ends with discussions about the politics, policy, personal behaviours and advocacy behind creating healthy and sustainable food systems. With a food systems approach to health and sustainability identified as a priority area for public health, this text introduces core knowledge for students, academics, practitioners and policy-makers from a range of disciplines including food and nutrition sciences, dietetics, public health, public policy, medicine, health science and environmental science"--
Includes bibliographical references and index.
Keywords: Food Supply; Sustainable Development; Food Quality; Healthy Diet; Health Equity